2014
DOI: 10.1016/j.apcatb.2013.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Azo-dye orange II degradation by the heterogeneous Fenton-like process using a zeolite Y-Fe catalyst—Kinetics with a model based on the Fermi's equation

Abstract: The degradation of Orange II dye (OII) by a heterogeneous Fenton-like process was studied using a catalyst with 5 wt.% of iron after ion-exchange in a Na-Y zeolite support. The catalyst was characterized by X-ray diffraction (XRD), N2 adsorption, atomic absorption spectroscopy and X-ray fluorescence (XRF). The effect of the initial concentrations of H2O2 and OII, pH and temperature on the degradation rate of OII was investigated by carrying out experiments in a batch reactor. The OII concentration histories (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 185 publications
(96 citation statements)
references
References 39 publications
9
75
1
4
Order By: Relevance
“…Results obtained allowed concluding that the zeolite catalyst is stable, as reported in similar studies [5], or even more stable. In fact, Idel-aouada et al [26] observed a little decrease of acid red 14 dye reduction (from 100 to 93% in the 1 st vs. 3 rd run, respectively) when using a Fe(II)-Y zeolite as catalyst, while other authors noticed some decay of activity with other supports like saponite clay [9]; activated carbons also proved to be stable [8,14].…”
Section: Stability Of the Catalystsupporting
confidence: 54%
See 3 more Smart Citations
“…Results obtained allowed concluding that the zeolite catalyst is stable, as reported in similar studies [5], or even more stable. In fact, Idel-aouada et al [26] observed a little decrease of acid red 14 dye reduction (from 100 to 93% in the 1 st vs. 3 rd run, respectively) when using a Fe(II)-Y zeolite as catalyst, while other authors noticed some decay of activity with other supports like saponite clay [9]; activated carbons also proved to be stable [8,14].…”
Section: Stability Of the Catalystsupporting
confidence: 54%
“…Moreover, under such conditions the formation of ferrous/ferric hydroxide complexes occurs, which lead to the deactivation of the ferrous catalyst [50]; moreover, the oxidation potential of the hydroxyl radical also decreases with increasing pH (2.65-2.80 at pH = 3 and 1.90 V at pH = 7) [11]. On the other hand, the decreased efficiency of the process at very acidic pH values may be related to the decreased generation of hydroxyl radicals, once the hydrogen peroxide forms the hydroperoxonium ion (H3O2 + ) by proton solvation, and therefore does not react with iron [5]. However, in terms of iron concentration in the effluent, lower pH values provide rather poor results (Figure 8 b), so that for pH = 1.5 the limit of 2 ppm of iron is exceeded, showing a great leaching of the initial iron present in the catalyst.…”
Section: Influence Of Phmentioning
confidence: 99%
See 2 more Smart Citations
“…[30] The increase of temperature promotes the generation of radicals and the subsequent attack to the dye molecules. [31] It can be found that complete dye degradation can be obtained at 30, 45 and 60 o C after 140 min. Despite the fact that the MB degradation at 30 o C is not as fast as those observed at higher temperatures, the performances of MB removal at 30 o C is chosen to carry out the following studies based on the fact that use of lower temperature reduces considerably associated larger scale operational cost and eliminate the possibility of catalyst leaching after prolonged operation times.…”
Section: Resultsmentioning
confidence: 89%